Potential Applications Of The Chemiluminescent Methods In Tumoral Diseases Investigation - J.L.S. ARAÚJO-FILHO; M.R. MELO-JUNIOR; L.B. CARVALHO JR (International Journal of Pharma and Bio Sciences, 2011)
Nowadays, in the clinic routine, protein biomarkers of efficacy, or mode of action, are used to better monitor and predict patient responses to drug treatment and diagnosis. Currently, the chemiluminescence biomarkers are applied for validation methods and screening. Here, was revised the development of the new analytical tool through immunological (antibody) and chemiluminescent methods combination, named chemiluminescence immunoassay (CLIA). In the tumoral process, increased expression of specific antigens is associated in patients with certain tumors. Thus, in our laboratories CLIA has been tested to study different tumoral lesions from glandular tissues, like prostate and thyroid. In conclusion, there is a great opportunity for introducing the adaptive chemiluminescence devices, since clinical diagnostics represents a huge, well-established and important analytical field.